The Effect of Modified Atmosphere Packaging and Addition of Rosemary Extract, Sodium Acetate and Calcium Lactate Mixture on the Quality of Pre-cooked Hamburger Patties during Refrigerated Storage - Muhlisin, (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The effect of modified atmosphere packaging (MAP; 30% CO(2)+70% N(2) or 100% N(2)) and an additive mixture (500 ppm rosemary extract, 3,000 ppm sodium acetate and 1,500 ppm calcium lactate) on the quality of pre-cooked hamburger patties during storage at 5°C for 14 d was evaluated. The addition of the additive mixture reduced aerobic and anaerobic bacteria counts in both 30% CO(2)-MAP (30% CO(2)+70% N(2)) and 100% N(2)-MAP (p<0.05). The 30% CO(2)-MAP was more effective to suppress the microbial growth than 100% N(2)-MAP, moreover the 30% CO(2)-MAP combined with additive mixture resulted in the lowest bacterial counts. The hamburger patties with additive mixture showed lower CIE L* and CIE a*, and higher CIE b* than those with no additive mixture. The 30% CO(2)-MAP tended to decrease the TBARS during storage regardless of the addition of additives. The use of 30% CO(2)-MAP in combination with additives mixture was effective for maintaining the quality and extending the shelf-life of pre-cooked hamburger patties.